ANTIBACTERIAL ACTIVITY OF BITTER LEAF (Vernonia amygdalina) EXTRACTS ON Escherichia coli AND Staphylococcus aureus - Raji, Modinat; Amoo, Florence Kemi; Adeniyi, Kamoru Abdulazeez; Amoo, Afeez Oladeji; Abdulrahman, M. I.; Mukthar, Ismail Sa’adatu; Baita, Nafisat; Adeleye, Adeniyi Olarewaju; Abba, Sa’adatu Yusuf (FUDMA JOURNAL OF SCIENCES, 2025)
In recent years, there has been a growing global health concern, necessitating the search for potent, resistance-free medicinal plants with antibacterial properties. This study evaluates the phytochemical and antibacterial properties of Vernonia amygdalina (bitter leaf) extracts as an alternative treatment for bacterial infections. Ethanolic and aqueous extracts of V. amygdalina leaves were prepared and subjected to phytochemical screening, revealing the presence of quinones, tannins, steroids, saponins, terpenoids, alkaloids, phenols, and flavonoids. The antibacterial activity was assessed against Staphylococcus aureus (gram-positive) and Escherichia coli (gram-negative) using the agar well diffusion method. Results showed that the highest inhibition zone (20 mm) was observed for the ethanolic extract at 200 mg/mL against S. aureus, while the aqueous extract exhibited a 10 mm inhibition zone against E. coli at the same concentration. The aqueous extract demonstrated moderate antibacterial activity, with inhibition zones of 20 mm and 12 mm against S. aureus and E. coli, respectively. In contrast, gentamicin, a standard antibiotic, produced inhibition zones of 36 mm and 33 mm. The study suggests that V. amygdalina exhibits stronger antibacterial activity against gram-positive S. aureus than gram-negative E. coli, likely due to tannins, saponins, and alkaloids. These findings support the medicinal potential of V. amygdalina and provide a scientific basis for its traditional use in bacterial infection treatment. Further research is recommended to isolate and characterize the bioactive compounds responsible for its antimicrobial effects.
Keywords: Antibacterial activity; antimicrobial resistance; medicinal plant; phytochemicals; Vernonia amygdalina